Productivity-employment link and asymmetric adjustments: the case of Indonesia, Malaysia and Thailand - Abdullah Yusof, Selamah (Research Science Press, 2010)
The theoretical link between employment and productivity can be bi-directional, and the effect of one on the other can be both positive and negative. Unemployment reduces productivity through reduction in spending on education and training, but improves productivity by removing the least productive firms from the economy. Meanwhile, an increase in productivity reduces the demand for labor as workers are more efficient, but leads to greater employment through an increase in production. This paper focuses on three south-east Asian countries, namely, Indonesia, Malaysia and Thailand to test the theory and applies cointegration and error correction models to determine the interactions between productivity and employment. It considers asymmetric adjustments since studies have shown that a long-run relationship may not be detected using cointegration analysis which assumes symmetric adjustments. The results indicate that no definite long term relationship can be established between employment and productivity for Indonesia and Thailand. However, a positive equilibrium relationship between productivity and employment is obtained for Malaysia. Both variables adjust to deviations from the long-run equilibrium value, but the way they adjust differs. Employment quickly adjusts to negative discrepancies, but is less readily to decrease. In contrast, productivity adjusts to positive discrepancies but displays persistence for negative discrepancies.